OVERCOMING ADMINISTRATIVE OBSTACLES IN FINANCING CROATIAN FARMERS AND ENTREPRENEURS: THE POLICY DIMENSION OF THE EUROPEAN UNION'S FUND ABSORPTION - Marko ŠOSTAR; Hrvoje BUDIĆ; Ines ŠKOKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The research aims to analyze the EU funding for agriculture as well as the administrative obstacles of the national public bodies in using these funds for Croatian family farms/entrepreneurship and the role of policymakers in increasing the efficiency of absorbing funds from this source. Administrative barriers that appear at the national level were analyzed, with an emphasis on those that arise in procedures when applying for EU fund competitions, the financial approval process, and the criteria and conditions of the competitions themselves. The data used in the empirical analysis included 284 respondents who were surveyed through a questionnaire. The respondents were private consultants working on the preparation and implementation of projects funded from EU funds and were surveyed based on their many years of experience. Consultants from all regions in Croatia were covered to ensure more reliable results. The results show that delays in the preparation of national strategic documents significantly affect the reduction of efficiency in the use of EU funds. The most significant impact on the reduction of efficiency in the absorption of funds from EU sources is due to unreliable publication plans, prolonged project application assessments, frequent changes to competition documentation, and competition misalignment with the possibilities and needs of potential applicants. In contrast, less influence comes from unclearly defined competition conditions and the way (model) competitions are announced. The research aims to assist national authorities and provide guidelines to reduce administrative barriers, making it easier to finance projects for companies, public institutions, and other potential applicants.